Successful Technopreneurship 2.0: Beyond buzzwords and technology - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
If entrepreneurship requires true grit, then technopreneurship – a new-age term that describes entrepreneurship in technology sectors – is quite likely the ultimate test, given the highly dynamic nature of technological innovation and its dependency on a host of external factors. Would the iPhone have succeeded without the App store? Could the Blu-Ray have taken off without the backing of major Hollywood studios? Will people buy GPS systems without maps? Such are considerations that technopreneurs have little influence over, but must always bear in mind because technology, in and of itself, bears little meaning for end-consumers.